Swamedikasi Dismenorea Primer pada Remaja Putri - Safitri, Safitri; Hayati, Fatihatul (Prosiding Seminar Kesehatan Nasional, 2024)
Self-medication or commonly referred to as self-medication is an alternative for people to treat a disease that is considered to be treatable by each individual. This study aims to determine how self-medication knowledge is carried out including: handling primary dysmenorrhea, reasons for using drugs, choosing drugs, sources of information for getting drugs, where to get drugs, duration of drug use, follow-up after self-medication, side effects of drugs, and storage of drugs in adolescent girls at SMA N 7 Kota Jambi. This research method uses an observational research type with a descriptive analysis method. The population of the study was 255 female adolescents in grades 10, 11, and 12 of SMAN 7 Kota Jambi. The research sample was 40 people with proportional random sampling technique. Data collection was carried out through a questionnaire from January to March 2024. The results of the study showed that the treatment carried out to overcome dysmenorrhea experienced was the use of traditional herbal medicine (45%), the reasons for using the medicine were easy, fast and practical (47.5), the choice of medicine in the form of turmeric and tamarind herbal medicine (55%), sources of information to get medicine based on personal experience were 15 (37.5%), the place to get medicine was a pharmacy (35%), the duration of use of medicine on days 1-3 of menstruation (82.5%), follow-up after self-medication choosing not to go to health services (87.5), side effects of the drug were drowsiness (32.5), and storage of medicine in original packaging, at room temperature, protected from the sun, and away from humidity was (42.5%). Further socialization is needed for adolescent girls so that they can handle primary dysmenorrhea correctly.